Crítica ontológica à teoria da democracia como valor universal de Carlos Nelson Coutinho - Magane, Felipe Toledo (2007)
In a historic moment in which the bourgeois autocracy of the country was rebuilding itself, in the year of 1979, a process started by the proclamation of political amnesty at the beginning of the government of João B. Figueiredo, an essay by Carlos Nelson Coutinho was published in issue number 9 of magazine Encontros com a Civilização Brasileira (meeting of Brazilian culture), entitled Democracy as an universal value . This essay is the very root of our present endeavor. It is an essay held by many positively or negatively as a watershed in left-wing Brazilian politics. The main purpose of this present research is to unveil the ideologic pattern of Coutinho s worldview, its ramifications and practical advent within the left-wing. There is also an added concern of salvaging an old debate of the European worker s movement about the validity, universality or class-related, of political democracy. Taking as a starting point the debates within German and Russian social-democracy, we considered the disputes between Rosa Luxemburg and Eduard Bernstein, and, later, Lenin s criticism of Kautsky. Furthermore, it is also our intention to remark on the influence exerted on Carlos Nelson Coutinho s theory by the trend of Euro-communism , particularly from the ideological output of the Italian Communist Party and its organic intellectuals . The project was based on a specific bibliographic research and in other historical documents, made through ontological criticism, containing an immanent analysis of the subject, its social determination and function in the evolving of the historical process. Sifting through Coutinho s concept-linking, we located many problematic appropriations, wherein concepts about art, taken from the works of 13 Karl Marx, were transposed to the sphere of politics. We made an effort to analyze Coutinho s limitations, with the aid of the ontologic lineaments of marxist thought. About onto-negative determination of politicity, with specify the limits of political democracy, not as ultimate liberty, due to its being supported by the pillars of a civil society driven by capital. The emancipation of mankind in general requires an association in which the free development of each is a condition for the development of all (Karl Marx)